Grazing and global change factors differentially affect biodiversity‐ecosystem functioning relationships in grassland ecosystems. (8th July 2022) - He, Miao; Pan, Yuhan; Zhou, Guiyao; Barry, Kathryn E.; Fu, Yuling; Zhou, Xuhui
Abstract: Grazing and global change (e.g., warming, nitrogen deposition, and altered precipitation) both contribute to biodiversity loss and alter ecosystem structure and functioning. However, how grazing and global change interactively influence plant diversity and ecosystem productivity, and their relationship remains unclear at the global scale. Here, we synthesized 73 field studies to quantify the individual and/or interactive effects of grazing and global change factors on biodiversity‐productivity relationship in grasslands. Our results showed that grazing significantly reduced plant richness by 3.7% and aboveground net primary productivity (ANPP) by 29.1%, but increased belowground net primary productivity (BNPP) by 9.3%. Global change factors, however, decreased richness by 8.0% but increased ANPP and BNPP by 13.4% and 14.9%, respectively. Interestingly, the strength of the change in biodiversity in response to grazing was positively correlated with the strength of the change in BNPP. Yet, global change flipped these relationships from positive to negative even when combined with grazing. These results indicate that the impacts of global change factors are more dominant than grazing on the belowground biodiversity‐productivity relationship, which is contrary to the pattern of aboveground one. Therefore, incorporating global change factors with herbivore grazing into Earth system models is necessary to accurately predict climate‐grassland carbon cycle feedbacks in the Anthropocene. Abstract : This study represents an extensive meta‐analysis about how grazing and three global change factors interactively affect biodiversity‐productivity relationships for both aboveground and belowground systems. We found that grazing reduced plant diversity and aboveground productivity but increased belowground productivity. Global change factors, however, decreased plant diversity but increased both aboveground and belowground productivity. Contrary to the relationship between diversity and aboveground productivity, the effect of global change is more important than grazing for the relationship between diversity and belowground productivity. These findings are helpful to incorporate herbivore grazing and global change factors into the prediction of climate‐grassland feedback in the Anthropocene.